2015
DOI: 10.1111/ijun.12069
|View full text |Cite
|
Sign up to set email alerts
|

Developing a rehabilitation programme for male urinary incontinence: detailed schemes and results on 122 patients

Abstract: Urinary incontinence (UI) is a common complication of prostatectomy. International guidelines suggest using pelvic floor muscle training (PFMT) as a first‐line intervention (grade A) to help patients reduce the involuntary urine leakages. In the literature it is hard to find a complete exercise scheme, with full details (e.g. body position during PFMT, how to avoid antagonist synergies), information on how to make exercises progressively more difficult, and data showing the efficacy of the whole programme. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 15 publications
(19 reference statements)
1
22
0
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations